2020
DOI: 10.1111/1755-6724.14604
|View full text |Cite
|
Sign up to set email alerts
|

Neoproterozoic Crustal Reworking and Growth in the Zhangbaling Uplift, Tan–Lu Fault Zone: Evidence from the Feidong Complex and Zhangbaling Group

Abstract: Intensive mid‐Neoproterozoic magmatism is the salient feature of the Yangtze Block, preserving abundant information about crustal reworking and growth. Zircon U–Pb–Lu–Hf isotope analysis was performed on material from the Feidong Complex (FDC) and Zhangbaling Group (ZBLG) of the Zhangbaling Uplift, in order to determine the age and magmatic source of the Neoproterozoic igneous rocks as well as the detrital provenance for the sedimentary rocks, to further provide important data for understanding the mid‐Neoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Over the last few decades, research on the Feidong Complex has mainly focused on Neoproterozoic magmatism and Mesozoic tectonic evolution (Cai et al, 2021;Li et al, 2020;Liu et al, 2015;Niu et al, 2020;Zhu et al, 2018). However, research on early basement rocks is limited, despite the significant role of their formation age in Moreover, recent research has identified large volumes of Neoproterozoic magmatic rocks with ages of 823-745 Ma within the Feidong Complex (Cai et al, 2021;Liu et al, 2015).…”
Section: Ages Of the Basement Rocksmentioning
confidence: 99%
“…Over the last few decades, research on the Feidong Complex has mainly focused on Neoproterozoic magmatism and Mesozoic tectonic evolution (Cai et al, 2021;Li et al, 2020;Liu et al, 2015;Niu et al, 2020;Zhu et al, 2018). However, research on early basement rocks is limited, despite the significant role of their formation age in Moreover, recent research has identified large volumes of Neoproterozoic magmatic rocks with ages of 823-745 Ma within the Feidong Complex (Cai et al, 2021;Liu et al, 2015).…”
Section: Ages Of the Basement Rocksmentioning
confidence: 99%
“…Thus, the TFZ could act as a conducting channel for the upwelled asthenosphere materials. That is, the collision and subduction between the NCP and SCP at the DOB and SOB first begun with the oceanic subduction before switching to the continent-continent type (Niu et al, 2020); later during the intra-continental collision, the deep mantle and/or recycled crustal material from the asthenospheric upwelling in the Mesozoic regional magmatism was injected into the crust through the previously formed shearing zone in the Zhangbaling area (Lü et al, 2013(Lü et al, , 2015Shi et al, 2013).…”
Section: Magma Upwelling Channelmentioning
confidence: 99%
“…Further geochronological information can be extracted from Early Cretaceous granites and granitic veins that intrude or crosscut the shear zone and have been dated between ca. 134 and 103 Ma (Niu et al., 2008; Zhu et al., 2010, 2018), which indicates the shear zone formed before 134 Ma.…”
Section: The Fucha Shan Shear Zonementioning
confidence: 99%
“…The Feidong complex consists mainly of plagioclase amphibolite, biotite‐plagioclase gneiss and hornblende‐plagioclase gneiss, with 2.6 and 2.0 Ga protoliths (Y. Shi et al., 2016; Tong & Xu, 2000; Tu et al., 2021; Ye et al., 2017; Q. Zhang et al., 2007) unconformably overlain by Middle‐Late Proterozoic phosphorous limestones (J. Xu et al., 1987, W. Xu et al., 2002; Q. Zhang et al., 2007). This rock package was intruded by bimodal magmas during the Neoproterozoic era (810 and 740 Ma) (Kang et al., 2013; L. Liu et al., 2015; Niu et al., 2020; Zhao et al., 2014). The Feidong complex records amphibolite‐facies metamorphism but the timing of peak metamorphism remains controversial and is variously suggested to be: (a) ∼688 Ma (Ge & Zhou, 1993), (b) 242 ± 26 Ma (Zhao et al., 2014), or (c) 167–133 Ma (Y. Shi et al., 2016).…”
Section: The Fucha Shan Shear Zonementioning
confidence: 99%
See 1 more Smart Citation